Evaluation of the Microbiological and Nutritional Quality of Fermented-Dried Lesser African Threadfin (Galeoides decadactylus) Used as Food Supplement in Southern Benin - DEGNON, GNIMABOU RENÉ; ADJOU, EULOGE SÈNAN; DAHOUENON-AHOUSSI, Edwige; SOUMANOU, MANSOUROU MOHAMED; FIOGBE, EMILE DIDIER (My University, 2014)
Lesser African threadfin (Galeoides decadactylus) is a nutritious marine fish, popular and widely used for dry- ing-fermentation. The present work aims to evaluate the nutritional and microbiological quality of dried-fer- mented Lesser African Threadfin, currently used in food preparing in southern Benin. Four major sites of dry- ing-fermentation fishes in southern Benin were investigated and dried-fermented Lesser African Threadfin was collected for quality control. Results indicated that the dried-fermented fishes were good sources of nutriments with a moisture content ranging from 44.62% ± 0.68% to 55.33% ± 0.23%. Proteins contents are ranged from 15.26% ± 0.32% to 22.95% ± 0.71%. All samples analyzed were rich in minerals such as magnesium, phosphorus, iron, with a higher content of calcium (1.23% ± 0.52% - 1.69% ± 0.38%). Statistical analyses showed significant difference (p < 0.05) between samples analyzed. Microbiological analyses revealed that the total flora count of samples ranged from 1.4 × 102 to 8.0 × 104 ufc/g. The enumeration of total coliforms and fecal coliforms indicated that samples were contaminated with enteric bacteria. The spores of anaerobic sulfite reducer’s and Staphylo- coccus aureus counts were less than 10 cfu/g with an absence of Salmonella spp. Based on results from the pre- sent study, microbiological standards must be put in place during the process of dried-fermented fishes. Then, it’s advisable that relevant quality control unit should be reactivated to assess the quality of ready-to-eat food, and particularly the fermented fishes in other to protect consumer’s health.
Keywords: Galeoides decadactylus; Drying-Fermentation; Nutritional and Microbiological Quality; Benin